Analisis Faktor Yang Mempengaruhi Pendapatan Masyarakat Pasca Tsunami - Fadli, Fadli (Faculty of Agriculture, Universitas Malikussaleh, 2013)
Analysis of factors influencing people’s income after tsunami. Income is the main factor in improving the walfare of society. Post-tsunami community life certainly very difficult, all sources of income and their property destroyed by the brunt of the tsunami waves. Human capital, physical capital and economic capital and social capital is also a key factor in increasing rural incomes post-tsunami. This study aims to analyze the factors that influence people’s income after the tsunami. Data were analyzed by regression analysis. The research show that social capital is a factor which significantly affect the increase in income after the tsunami.